الحماية القانونية لمستخدمي وسائل التواصل الاجتماعي في ظل القانون 20-05 المؤرخ في 28 أفريل 2020 - شينون أكرم (جامعة محمد بوضياف بالمسيلة, 2025)
تسلط هذه الدراسة الضوء على الإطار القانوني لحماية وسائل التواصل الاجتماعي في الجزائر، من خلال تحليل النصوص التشريعية ذات الصلة، وعلى رأسها القانون رقم 20-05 المتعلق بمكافحة التمييز وخطاب الكراهية، تم تناول الموضوع من زاوية نظرية تشمل المفاهيم العامة والتحديات القانونية، ومن زاوية تطبيقية من خلال دراسة وقائع واقعية عكست مدى تفعيل النصوص القانونية على أرض الواقع، وقد خلصت الدراسة إلى أن المشرع الجزائري اتخذ خطوات مهمة لتقنين الفضاء الرقمي، غير أن التطبيق لا يزال يواجه صعوبات تتعلق بالغموض التشريعي، وضعف الرقابة التقنية، ومحدودية التعاون مع المنصات الرقمية الكبرى، توصي الدراسة بضرورة إصدار نصوص تنظيمية مكمّلة، وتطوير القدرات التقنية والبشرية للجهات المعنية، بما يضمن التوازن بين حرية التعبير والحماية القانونية لمستخدمي وسائل التواصل This study highlights the legal framework for the protection of social media in Algeria by analyzing relevant legislative texts, primarily Law No. 20-05 related to combating discrimination and hate speech. The topic is approached from a theoretical perspective, covering general concepts and legal challenges, and from a practical perspective through the study of real cases that reflect the extent of the implementation of the legal provisions on the ground. The study concludes that the Algerian legislator has taken important steps to regulate the digital space; however, the implementation still faces difficulties related to legislative ambiguity, weak technical oversight, and limited cooperation with major digital platforms. The study recommends the issuance of complementary regulatory texts and the development of technical and human capacities of the concerned authorities to ensure a balance between freedom of expression and legal protection for social media users